Why Cataloguing Is Cool. Issue 4 (2nd October 2021) - Attar, Karen
ABSTRACT: Cataloguing has lost status over the years, particularly the cataloguing of machine-press books in a standard library setting. This information-in-practice article redresses the view that cataloguing is a routine clerical activity, primarily in the context of modern special collections. It demonstrates from experience how detailed cataloguing furthers research, teaching, bibliography, digitisation, and engagement. Cataloguing saves users time and money and assists preservation by reducing the handling of books. Ultimately, it also saves library staff time. For the library overall, attention to this core activity shows an investment in potential future use, and for practitioners this is a worthy and worthwhile task.